ANALYSIS OF THE PRESENCE OF CRYPTOCOCCUS NEOFORMANS IN BIRDS EXCRETES IN THE GOOD JESUS SQUARE LOCATED IN THE CENTRAL REGION OF THE CITY OF ANÁPOLIS, GOIÁS (CIPEEX, 2022)
CRYPTOCOCCUS NEOFORMANS IS A PATHOGENIC FUNGUS WITH A BROAD GEOGRAPHIC DISTRIBUTION. IT HAS AN ENCAPSULATED OVAL SHAPE, WHICH CAN BE FOUND IN CONTAMINATED SOIL WITH BIRD FECES, MAINLY DOMESTIC PIGEONS (COLUMBA LIVIA), AND IS CONSIDERED THE ETIOLOGICAL AGENT OF CRYPTOCOCCOSIS. CRYPTOCOCCOSIS IS A SYSTEMIC INFECTION THAT USUALLY AFFECTS IMMUNOCOMPROMISED INDIVIDUALS. CONTAMINATION MAY OCCUR AFTER INHALATION OF FUNGUS PROPAGULES / SPORES RESULTING IN PRIMARY INFECTION IN THE RESPIRATORY SYSTEM AND THEN SPREADING INTO THE BLOODSTREAM REACHING OTHER ORGANS. IT WAS A RARE DISEASE, BUT CONFIRMED CASES HAVE PROGRESSIVELY INCREASED, WITH THE ONSET OF AIDS (ACQUIRED IMMUNODEFICIENCY SYNDROME) IN THE 1980S, AND THE ADVENT OF IMMUNOSUPPRESSIVE THERAPIES, BECOMING NOW AN EPIDEMIOLOGICALLY IMPORTANT DISEASE. WITH THE HIGH PREVALENCE OF BIRDS IN URBAN AREAS, THE HIGH CONCENTRATION OF C. NEOFORMANS IN POULTRY FECES AND THE SEVERITY OF THE DISEASE IN HUMANS, A GROWING INTEREST IN THE STUDY OF THE RELATIONSHIP BETWEEN THESE FACTORS IS OBSERVED. THEREFORE, THE PRESENT STUDY AIMS TO PERFORM QUALITATIVE ANALYZES TO IDENTIFY THE PRESENCE OF C. NEOFORMANS IN BIRD EXCRETA, COLLECTED IN A SQUARE LOCATED IN THE CENTRAL REGION OF THE CITY OF ANÁPOLIS, GOIS. SINCE THE CITY SQUARES HAVE A LARGE QUANTITY OF PIGEONS IT IS EXTREMELY IMPORTANT TO VERIFY THE OCCURRENCE OF CONTAMINATION OF THE FECES OF THESE BIRDS PRESENT IN THE SQUARES, BECAUSE IT IS A PLACE OF RECREATION, MAINLY BECAUSE OF THE ELDERLY AND CHILDREN THAT TRANSIT IN THE PLACE. THE METHODOLOGY ADOPTED WAS QUALITATIVE ANALYTICAL EXPERIMENTAL CHARACTER. STOOL SAMPLES WERE COLLECTED AT BOM JESUS SQUARE IN THE CITY OF ANÁPOLIS, GO AND ANALYZED AT THE MICROBIOLOGY LABORATORY OF CENTRO UNIVERSITÁRIO DE ANÁPOLIS - UNIEVANGLICA. THE SAMPLES WERE COLLECTED DURING THE SECOND HALF OF 2018, WITH A MASK, GLOVES AND STERILE FLASKS, IN THREE DIFFERENT PLACES, WITH THREE SAMPLES AT EACH SITE, TOTALING NINE SAMPLES. THEY WERE SUBMITTED TO DIFFERENT TESTS, SUCH AS CULTIVATION IN SABOURAUD DEXTROSE AGAR, FOLLOWED BY THE URFIQUE TEST AND THE CONFIRMATORY TEST WITH INK NANQUIM. THE RESULTS OF THE TESTS PERFORMED UP TO THE PRESENT MOMENT DID NOT SHOW ANY PRESENCE OF C. NEOFORMANS IN SABOURAUD AGAR DEXTROSE AND UR. TO INDICATE PRESENCE OF C. NEOFORMANS SABOURAUD AGAR IT IS NECESSARY TO FIND THE PRESENCE OF SMOOTH, MOIST, SHINY COLONIES, FROM CREAM TO BROWN. HOWEVER, IT WAS NOT POSSIBLE TO IDENTIFY THE PRESENCE OF COLONIES OF C. NEOFORMANS IN THIS TEST. THE UREASE TEST TO BE CONSIDERED POSITIVE REQUIRES A TURNING TO PINK OR RED. NO COLOR CHANGE WAS IDENTIFIED IN THE TEST, INDICATING ABSENCE OF C. NEOFORMANS IN THE ANALYZED SAMPLES. THE DIRECT INK EXAMINATION OF CHINA OR INK HAS NOT YET BEEN DONE. FOR POSITIVE RESULTS, WE EXPECT TO FIND OVAL OR ROUND CELLS IN THE SLIDES. THE PRESENT WORK IS STILL ONGOING, BUT IT IS HOPED THAT WHEN IT IS FINALIZED, THE RESULTS WILL ALL BE NEGATIVE, SO THAT PEOPLE WHO TRAVEL ON THE SPOT DAILY ARE NOT AT RISK OF CONTRACTING THE DISEASE.
Keywords: Cryptococcus. Cryptococcosis. Excreta.